PENGELOLAAN PEMBELAJARAN KURSUS DALAM MENUMBUHKAN KEMAMPUAN BERWIRAUSAHA LULUSAN KURSUS KOMPUTER DESAIN GRAFIS DI LKP IKMA MAJALAYA - Ariyandi, Eneng Halimah; Saepudin, Asep; Komar, Oong (PEDAGOGIA, 2017)
The background from this research because in the era of the business and industrial world today need human resources who competent and qualified. Today, many agencies are developing courses in Indonesia, one of the LKP IKMA Majalaya located in the district of Majalaya. IKMA is organizing various programs of courses, such as computer courses, accounting courses, and tutoring. IKMA also organizes community entrepreneurship program in cooperation with the government to reduce unemployment in the region of Majalaya. The program in the form of computer graphic design courses. This research aims to 1) describe the management learning courses in fostering entrepreneurship skills of graduates; 2) describe the entrepreneurship skills of graduates after the course; 3) know the supporting factor and inhibiting factor in fostering entrepreneurship skills of graduates. The method used is a descriptive method with qualitative approaches and techniques of collecting data through interviews, observation, and documentation. Subjects numbered four people consisting of one manager, one instructor and two graduates. Based on the processing of data and research results, obtained the following results. The First, activities of manager in management course learning to foster entrepreneurship skills of graduates include partnership building, provision of infrastructure and capital assistance for the graduate. The Second, emergence of entrepreneurship skills of graduates are characterized by traits entrepreneurs, namely confidence, task-oriented and results, risk-taking, leadership, originality and oriented to the future. Third, supporting factors consist of adequate infrastructure, and LKP has strategic locations. Furthermore, inhibiting factor consists of a shortage of human resources, especially instructors and prone to flooding.